2021
DOI: 10.32598/sija.2020.16.3.2190.2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Integrated and Comprehensive Geriatric Care Program of Ministry of Health on Physical and Mental Health of Older Adults in Golestan Province

Abstract: Objectives: In order to maintain and improve older adults’ health, the integrated and comprehensive geriatric care program has been developed and run by ministry of health. The present study was conducted to evaluate the effectiveness of this program on physical and mental health of older adults in Golestan province in 2019. Methods & Materials: The present retrospective cohort study employed a multistage clustered random sampling technique to obtain 500 e-health records of older adults during 2017-2019. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…One of the most important resources for supporting older adults is the health care system. [ 34 ] In this study, this system did not have adequacy for the vulnerability of the older adults following the death of a child. Iranian healthcare centers have not effectively integrated comprehensive geriatric care programs for mental health of older adults.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…One of the most important resources for supporting older adults is the health care system. [ 34 ] In this study, this system did not have adequacy for the vulnerability of the older adults following the death of a child. Iranian healthcare centers have not effectively integrated comprehensive geriatric care programs for mental health of older adults.…”
Section: Discussionmentioning
confidence: 82%
“…Iranian healthcare centers have not effectively integrated comprehensive geriatric care programs for mental health of older adults. [ 34 ] Despite the emphasis of experts on home care and its benefits for older adults, this program has not yet been implemented in Iran. [ 35 ] Inadequate home care was particularly salient during the COVID-19 pandemic and may increase the risk for poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They highlighted issues such as the non-implementation of home care programs and a lack of educational and recreational opportunities for older adults. A study conducted in Iran revealed that integrated and comprehensive mental health care for older adults was not effective enough [ 15 ]. Also, older adults’ home care programs have not yet been implemented in Iran [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are crucial in providing care for older adults in Iran, but studies suggest that mental health services may not be effective enough [ 15 ]. While nursing models for coping exist, they tend to be general and not specific to older adults [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%